Atherosclerosis velocity and its prognostic value - Gamkrelidze, Marika; Sulashvili, Nodar; Sulashvili, Marika (Caucasus Journal of Health Sciences and Public Health, 2018)
In most cases atherosclerosis is the underlying cause of vascular diseases, including heart disease and stroke. It is believed that endothelial injury is the earliest change in the artery wall and that this precedes the formation of lesions of atherosclerosis. In this review article, we summarize the existing evidence regarding atherosclerosis velocity and discuss the importance of this issue. We explore the evidence that encompasses all the three essential atherosclerosisrelated factors, namely time/ duration of atherosclerosis progression, plaque volume, and plaque vulnerability, in one study. Atherosclerosis velocity includes the time-dependent development of the plaque from endothelial injury to acute arterial thrombosis. All previous investigations have focused only on the probability of plaque regression at the expense of almost neglecting the parameter of time. We suggest that future studies could be designed based on the probable association between statin therapy and atherosclerosis velocity reduction. The concept of atherosclerosis velocity should be applied in further experiments, especially in experimental models. If investigators focus on the concept of “time” for atherosclerosis development, it may result in considerable prevention of atherosclerosis-related morbidity/mortality